Gemtuzumab ozogamicin in first-line treatment of CBF-AML: insights from a retrospective multi-center analysis : acute myeloid leukemia - Ronnacker, Julian; Muller, Philippe J.; Mikesch, Jan-Henrik; Zukunft, Sven; Weinbergerová, Barbora; Šrámek, Jiří; Valka, Jan; Novak, Jan; Zak, Pavel; Szotkowski, Tomas; Koristek, Zdenek; Krekeler, Carolin; et al. (Leukemia, 2025)
The addition of gemtuzumab ozogamicin (GO) to intensive chemotherapy (IC) has become a mainstay in treating patients with core binding factor acute myeloid leukemia (CBF-AML). However, evidence for the efficacy of GO in this particular subgroup is primarily based on meta-analytic data from different trials conducted more than a decade ago. In this registry-based study, we evaluated the impact of adding GO to IC in 265 CBF-AML patients from the SAL, AMLCG, and CELL cooperative study groups. Patients receiving GO had a 2-year overall survival of 90% compared with 80% in those without GO (hazard ratio [HR] 0.45, 95% confidence interval [CI] 0.21-0.95, P = 0.036) and a 2-year event-free survival of 51% versus 36% (HR 0.69, 95% CI 0.48-0.99, P = 0.046). While complete remission rates in GO vs. non-GO patients were comparable (89% vs. 90%, P = 0.81), more GO patients achieved measurable residual disease-negative remission (77% vs. 49%, P < 0.001), resulting in numerically reduced cumulative incidence of relapse (HR 0.67, 95% CI 0.43-1.02, P = 0.06). Despite delayed platelet recovery, high-grade toxicities were not increased in GO-treated patients. These findings support the integration of GO into treatment protocols for IC-eligible patients with CBF-AML.